A abordagem da biodiversidade nos resumos públicos dos planos de manejo FSC no Brasil : uma análise crítica - Alves, Telma Regina (Universidade Federal de São Carlos, 2016)
The silviculture activity, as well as other economic activities (industrial, agrarian, farming, etc.), can cause environmental impacts, both positive and negative, according to a number of circumstances, such as in relation to the conditions prior to planting, water regime in the region, the biome of insertion of the activity, the management techniques employed, the integration of the local population, among others. Plantations of exotic species (ex. genera Eucalyptus and Pinus) have been the subject of severe criticism regarding the possible reduction of biodiversity. These criticisms have arisen from situations and relationships that conflict that have occurred, for decades, between those responsible for the implementation and use of these plantations on one side and the other people aware of the need for preservation of biodiversity. In this study we selected 15 Brazilian companies that are certified to the Forest Stewardship Council (FSC) with the aim of assessing whether the Management Plans from forests certified by the Forest Stewardship Council (FSC) had evidence of the use of the results of monitoring of biodiversity (especially fauna) in interventions of forest management aimed at biological conservation. The method used was the documentary analysis of the Public Summaries of the Management Plans, between the years of 2011 to 2015, available on the internet. Among the several results obtained, of note is the fact that the 15 forestry companies, 13 (87%) conducted an inventory of qualitative and quantitative aspects of wild fauna, and analyzing the total hectares of areas monitored in relation to the total number of areas in plantation of eucalyptus, in 8 (53%) forestry companies monitoring is conducted in areas that have a range of 5% to 47% of the areas under certification. We can observe, through critical analysis of their management plans, in which they are sampling of static form the structure of biodiversity, through lists of species. It concludes that there are no concrete evidence of the use of information obtained through monitoring of fauna for making decisions about the best ways of intervention of forest management, indicating uncertainty when the real possibility of same to assist in the conservation of biodiversity. This way, was proposed a protocol model for monitoring of fauna, with specific methodologies for the group of wild mammals. In this case, the results can be used in the assessment of the impacts of forest management of forestry companies contributing to the fitting of the form of forest management compatible with the maintenance of its biodiversity.
Keywords: Certificação; Manejo florestal; Fauna; Mamífero silvestre; Monitoramento; Plano de manejo; Protocolo; Certification; Forest management; Wild mamal; Monitoring; Management plan; Protocol; CIENCIAS BIOLOGICAS::ECOLOGIA